2021
DOI: 10.1371/journal.pone.0256739
|View full text |Cite
|
Sign up to set email alerts
|

Platelets’ RNA as biomarker trove for differentiation of early-stage hepatocellular carcinoma from underlying cirrhotic nodules

Abstract: Background & aims Among the multiplicity of factors involved in rising incidence of hepatocellular carcinoma (HCC)-the second deadliest cancer, late diagnosis of early-stage HCC nodules originating from late-stage cirrhotic nodules is the most crucial. In recent years, Tumor-educated platelets (TEPs) have emerged as a strong multimodal tool to be used in liquid-biopsy of cancers because of changes in their mRNA content. This study assessed the reliability of selected mRNA repertoire of platelets as biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Likewise, mRNAs such as CTNNB1, Rho A, SPINK1, IFITM3, and SERPIND1 contained in TEPs could permit earlier diagnosis of HCC from cirrhotic nodules. This result was evidenced in a 50-person cohort comprised of healthy subjects, patients with HCC, and cirrhosis [217]. By the bioinformatic analysis of platelet miRNAs, 250 miRNAs with differential expression were identified in blood samples from HCC patients and controls.…”
Section: Platelets and Tepsmentioning
confidence: 90%
“…Likewise, mRNAs such as CTNNB1, Rho A, SPINK1, IFITM3, and SERPIND1 contained in TEPs could permit earlier diagnosis of HCC from cirrhotic nodules. This result was evidenced in a 50-person cohort comprised of healthy subjects, patients with HCC, and cirrhosis [217]. By the bioinformatic analysis of platelet miRNAs, 250 miRNAs with differential expression were identified in blood samples from HCC patients and controls.…”
Section: Platelets and Tepsmentioning
confidence: 90%
“…In recent years, TEP RNA has become a research hotspot as a biomarker in tumour detection. It has been reported that platelet RNA can be used as a biomarker to distinguish early liver cancer from nodules of cirrhosis [21]. Sidra Asghar et al found that AKT expression in platelets of early HCC was reduced by 0.6 times and PI3K expression was reduced by 0.65, indicating a potential as diagnostic markers for early HCC [22].…”
Section: Discussionmentioning
confidence: 99%
“…Across cancer types, studies stated the valuable role of TEPs in carrying tumor mutational signatures as RNA profiles and indicated their potential role fit to be used for pan-cancer diagnostic utilities ( Best et al, 2015 ). Many studies in the scientific domain report mRNA profile changes in TEPs in various cancer types, such as non-small cell lung cancer (NSCLC) ( Luo L. et al, 2018 ; Xue et al, 2018 ; Dong et al, 2021 ), breast cancer ( Mendoza-Almanza et al, 2020 ), liver cancer ( Best and Wurdinger, 2020 ; Waqar et al, 2021 ), and glioma ( Campanella et al, 2020 ). Some studies have also investigated and found the role of medium-sized extracellular vesicles (EVs) (mEVs) exuviated by platelets activated by thrombins to carry prognostic clues ( Contursi et al, 2023 ).…”
Section: Tumor-educated Plateletsmentioning
confidence: 99%